The Analysis of Reliability Factorâ€™s Testing of An Academic Information System - Rofiah, Habibatur; Arifin, Hendra Dea; Muhsina, Elvanisa Ayu; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2016)
Academic information system of STMIK El Rahma College is a software which has function to make academic access activities easier. The system has no good quality yet. For example, several menus are unable to be opened.Â  Furthermore, the system has no error notification upon several menus. Hence testing software is necessitated to examine the reliability in operating of the system. McCall method has precision and detail which can be used to examine and assure the reliability of the academic information system of STMIK El Rahma. This research uses a testing procedure plan of software to obtain the reliability degree of the academic information system of STMIK El Rahma for SIMAK menu. The result of the reliability degree of the software is 49,29 %. It is obtained by several percentages such as 96% Accuracy, 0% Consistency, 62.96% Error Tolerance, 43,75% Modularity, and 43,75% Simplicity. The fivepercentages are divided by 5.